Characteristics of CO2‐driven cold‐water geyser, Crystal Geyser in Utah: experimental observation and mechanism analyses. Issue 3 (20th February 2013) - Han, W. S.; Lu, M.; McPherson, B. J.; Keating, E. H.; Moore, J.; Park, E.; Watson, Z. T.; Jung, N.‐H.
Abstract: Geologic carbon capture and storage (CCS) is an option for reducing CO2 emissions, but leakage to the surface is a risk factor. Natural CO2 reservoirs that erupt from abandoned oil and gas holes leak to the surface as spectacular cold geysers in the Colorado Plateau, United States. A better understanding of the mechanisms of CO2 ‐driven cold‐water geysers will provide valuable insight about the potential modes of leakage from engineered CCS sites. A notable example of a CO2 ‐driven cold‐water geyser is Crystal Geyser in central Utah. We investigated the fluid mechanics of this regularly erupting geyser by instrumenting its conduit with sensors and measuring pressure and temperature every 20 sec over a period of 17 days. Analyses of these measurements suggest that the timescale of a single‐eruption cycle is composed of four successive eruption types with two recharge periods ranging from 30 to 40 h. Current eruption patterns exhibit a bimodal distribution, but these patterns evolved during past 80 years. The field observation suggests that the geyser's eruptions are regular and predictable and reflect pressure and temperature changes resulting from Joule–Thomson cooling and endothermic CO2 exsolution. The eruption interval between multiple small‐scale eruptions is a direct indicator of the subsequent large‐scale eruption.